Hepatocellular carcinoma: Clinical-pathological features and HIV infection in Mozambican patients,. (2019) - Cunha, Lina; Carrilho, Carla; Bhatt, Nilesh; Loforte, Michella; Maueia, Cremildo; Fernandes, Fabíola; Guisseve, Assucena; Mbofana, Francisco; Maibaze, Fatima; Mondlane, Liana; Ismail, Muhammad; Dimande, Luzmira; et al.
Highlights: Mozambique is a historical hotspot for liver cancer in sub Saharan Africa. Hepatitis B virus is still the main risk factor. Co-infection with human immunodeficiency virus leads to a 4–5 years earlier onset of the tumor. Abstract: Background and aims: : Mozambique had been ranked among the countries with the highest global incidence of HCC with chronic hepatitis B infection and high exposure to aflatoxin-B1 (AFB1) being major risk factors. Indeed, HCC remains one of the most frequent cancer in Maputo. On the other hand, Mozambique has a high prevalence of infection with Human Immunodeficiency virus (HIV). Our study aims to describe the epidemiology, clinicopathological and serological features of patients with HCC in Maputo Central Hospital and its relationship with HIV. Methods: : A series of 206 patients, diagnosed with HCC via fine needle aspiration, were consecutively included in the study. Patient data was collected using a questionnaire and all patients were tested for HBV, HCV, HIV. Results: : Median age was 49 years old and the M: F sex ratio was 2.4. A total of 114 (56.2%) of the patients were HBsAg positive. Hepatitis C antibodies were present in 8.9% of cases, and co-infection with HBV and HCV (HBsAg/anti-HCV) was observed in 4 (2.0%) cases. The remainder, 36.3%, were neither hepatitis B- nor C-related. HIV was detected in 34 cases (18.0%) cases. HIV-HBV or HIV-HCV co-infections were observed in 22 (68.8%) and 2 (6.2%) cases. Overall, positivity for HIV was associated with younger age, and especially in patients with HBsAg+/anti-HCV+. Conclusions: : Our data emphasize the need for a reinforcement of secondary prevention measures in Mozambique. Serological screening for HBV in people born before universal anti-hepatitis B immunization (2001), effective screening, and specific management in HIV(+) patients are urgently needed.